Listening, not Lurking: The Neglected Form of Participation - Crawford, Kate (Cultures of Participation, 2011)
To speak of participation today raises a series of questions on how the presence and use of new media affect modes of social participation. From a variety of theoretical, empirical and methodological perspectives, the contributions in this volume explore participation in different social realms – from everyday life, interpersonal relationships, work and leisure activities to collective and political action. This collection demonstrates that participation is a localised notion, assuming a multitude of shapes under a variety of technological, political, socio-economic, linguistic and cultural conditions.